2010
DOI: 10.1063/1.3496029
|View full text |Cite
|
Sign up to set email alerts
|

Persistent photoconductivity in Hf–In–Zn–O thin film transistors

Abstract: Passivated Hf–In–Zn–O (HIZO) thin film transistors suffer from a negative threshold voltage shift under visible light stress due to persistent photoconductivity (PPC). Ionization of oxygen vacancy sites is identified as the origin of the PPC following observations of its temperature- and wavelength-dependence. This is further corroborated by the photoluminescence spectrum of the HIZO. We also show that the gate voltage can control the decay of PPC in the dark, giving rise to a memory action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 21 publications
5
120
1
Order By: Relevance
“…In terms of bond strength to oxygen atoms, Hf doping is also expected to have similar effects to Si doping. [31][32][33] However, to clarify the carrier transport in the present InO xbased semiconductors based on thermal activation, energy band diagrams, and local atomic structure, we will discuss further characterization, such as low temperature I-V measurements, 34 Hall measurements, 35,36 and X-ray absorption spectroscopy, 13,37 in another report. In conclusion, we fabricated amorphous oxide TFTs based on InO x semiconductors doped with Ti, W, or Si atoms.…”
mentioning
confidence: 99%
“…In terms of bond strength to oxygen atoms, Hf doping is also expected to have similar effects to Si doping. [31][32][33] However, to clarify the carrier transport in the present InO xbased semiconductors based on thermal activation, energy band diagrams, and local atomic structure, we will discuss further characterization, such as low temperature I-V measurements, 34 Hall measurements, 35,36 and X-ray absorption spectroscopy, 13,37 in another report. In conclusion, we fabricated amorphous oxide TFTs based on InO x semiconductors doped with Ti, W, or Si atoms.…”
mentioning
confidence: 99%
“…In the ionization oxygen vacancy (V O ) model for the LS insta- photo-generated electrons increase the conductivity in the channel [7][8][9]. The enhanced conductivity is known to be persistent because the state transforming from V O 2+ to V O 0 requires a large amount of energy to change the electron configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Although a-IGZO TFTs have such desirable properties, the instability of their threshold voltage (V TH ) under illumination with light can be a critical obstacle for their use in displays because the devices are exposed to ambient light during operation. Recently, several studies have reported on the V TH instability under a negative bias and under illumination stress (NBIS), and the results can be summarized into three models where the degradation is caused by (1) light-induced oxygen interstitial generation [4]; (2) trapping of a photo-generated hole [5,6]; and (3) an ionization oxygen vacancy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As to this slow photoresponse, there are some reports that describe the relaxation of photocurrent is caused by deep trap levels in the IGZO [11,17]. Figure 3 shows the result of measuring photocurrent in the IGZO.…”
Section: -1 Photoresponse Of Igzo Filmmentioning
confidence: 99%